Auger Electrons Constructed Active Sites on Nanocatalysts for Catalytic Internal Radiotherapy. Issue 10 (6th April 2020) - Su, Weiwei; Wang, Han; Wang, Tao; Li, Xiao; Tang, Zhongmin; Zhao, Shuai; Zhang, Meng; Li, Danni; Jiang, Xingwu; Gong, Teng; Yang, Wei; Zuo, Changjing; et al.
Abstract: Excess electrons play important roles for the construction of superficial active sites on nanocatalysts. However, providing excess electrons to nanocatalysts in vivo is still a challenge, which limits the applications of nanocatalysts in biomedicine. Herein, auger electrons (AEs) emitted from radionuclide 125 ( 125 I) are used in situ to construct active sites in a nanocatalyst (TiO2 ) and the application of this method is further extended to cancer catalytic internal radiotherapy (CIRT). The obtained 125 I‐TiO2 nanoparticles first construct superficial Ti 3+ active sites via the reaction between Ti 4+ and AEs. Then Ti 3+ stretches and weakens the OH bond of the absorbed H2 O, thus enhancing the radiolysis of H2 O molecules and generating hydroxyl radicals (OH). All in vitro and in vivo results demonstrate a good CIRT performance. These findings will broaden the application of radionuclides and introduce new perspectives to nanomedicine. Abstract : A simple and highly efficient catalytic internal radiotherapy (CIRT) is developed by 125 I‐labeled TiO2 nanoparticles. Auger electrons from 125 I react with Ti 4+ in TiO2 and construct superficial active sites of Ti 3+ . The generated Ti 3+ decreases the energy barriers of H2 O and contributes to the generation of OH upon γ‐rays irradiation, thus enhancing the antitumor effect of IRT.